Investor Competence, Trading Frequency, and Home Bias - Graham, John R.; Harvey, Campbell R.; Huang, Hai (Management Science, 2009)
People are more willing to bet on their own judgments when they feel skillful or knowledgeable. We investigate whether this “competence effect” influences trading frequency and home bias. We find that investors who feel competent trade more often and have more internationally diversified portfolios. We also find that male investors, and investors with larger portfolios or more education, are more likely to perceive themselves as competent than are female investors, and investors with smaller portfolios or less education. Our paper also contributes to understanding the theoretical link between overconfidence and trading frequency. Existing theories on trading frequency have focused on one aspect of overconfidence, i.e., miscalibration. Our paper offers a potential mechanism for the “better-than-average” aspect of overconfidence to influence trading frequency. In the context of our paper, overconfident investors tend to perceive themselves to be more competent, and thus are more willing to act on their beliefs, leading to higher trading frequency.